Disseminated Coccidioidomycosis Following Insufficient Treatment at Initial Presentation: Case Report. (August 2020) - Dev, Ameesh; Janysek, Dawn; Gnecco, James; Haghayeghi, Kamyar
A 35-year-old male presented to our university hospital with night sweats, fevers, ulcerated skin lesions to the lower mouth and posterior neck, shortness of breath, and an enlarging cervical lymph node. The patient was evaluated 2 months prior for respiratory symptoms, cervical lymphadenopathy, and skin lesions resulting in a diagnosis of primary pulmonary coccidioidomycosis and was treated with a 4-week course of fluconazole. On presentation to our hospital, initial laboratory test results revealed leukocytosis, increased liver enzymes, elevated inflammatory markers, and hypercalcemia. Computed tomography scan of the chest revealed lung nodules in a miliary pattern and prominent mediastinal lymphadenopathy. Magnetic resonance imaging revealed multiple vertebral and iliac bone lesions, as well as bilateral psoas muscle lesions. Serum ELISA (enzyme linked immunosorbent assay) detected elevated serological markers against coccidioides, and sputum culture revealed coccidioides arthroconidia, confirming the presence of an acute coccidioides infection. Biopsy of the right iliac crest and cervical lymph node revealed spherules resembling coccidioides, escalating the diagnosis to disseminated coccidioidomycosis. The patient's hospital course was complicated by septic shock, acute respiratory distress syndrome requiring several days of mechanical ventilation, and acute kidney injury. He was ultimately treated with several weeks of voriconazole and liposomal amphotericin-B. He made a full recovery and was discharged on an extended course of oral voriconazole. Our case highlights the importance of recognition and appropriate treatment duration of disseminated coccidioidomycosis at initial presentation. Failure to do so may lead to increased morbidity and mortality.